Understanding Regional and Seasonal Variability Is Key to Gaining a Pan-Arctic Perspective on Arctic Ocean Freshening - Brown, Kristina A.; Holding, Johnna M.; Carmack, Eddy C. (Frontiers in Marine Science, 2020)
The Arctic marine system is large and heterogeneous, harsh and remote, and now changing very rapidly, all of which contribute to our current inadequate understanding of its basic structures and functions. In particular, many key processes within and external to the Arctic Ocean are intrinsically linked to its freshwater system, which itself is undergoing rapid and uncertain change. The role of the freshwater system (delivery, disposition, storage, and export) in the Arctic Ocean has recently received significant attention; however, due to the fact that few studies are able to cover all regions and seasons of the Arctic Ocean equally, we still lack an accessible, unified pan-Arctic representation generalizing the impacts of freshwater on the upper Arctic Ocean where many biological and geochemical interactions occur. This work seeks to distill our current understanding of the Arctic freshwater system and its impacts into conceptual diagrams which we use as a basis to speculate on the impact of future changes. We conclude that inclusion of regional and seasonal variability is required in order to gain a pan-Arctic perspective on the physical-geochemical-biological state of the upper Arctic Ocean. As an example of regionality, enhanced stratification due to freshening will be more important in the Pacific influenced Amerasian Basin, which stores the bulk of the freshwater burden, while the Atlantic influenced Eurasian Basin will experience more consequences from increases in incoming heat. River influenced coastal regions will experience a mosaic of these and other biogeochemical effects, whereas glacial fjords may follow their own unique trajectories due to the loss of upwelling mechanisms at glacial fronts. As an example of seasonality, the continued modulation of the sea ice freeze-melt cycle has increased the seasonal freshwater burden in the deep basins dramatically as the system progresses towards ice-free summer conditions, but will eventually reverse, reducing the seasonal flux of freshwater by more than half in a future, perennially ice-free ocean. It is our goal that these conceptualizations based on the current state-of-the-art will drive hypothesis-based research to investigate the physical-biogeochemical response to a changing freshwater cycle in a future Arctic Ocean with greatly reduced ice cover.